2017
DOI: 10.1371/journal.pbio.2002429
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic loss and gain of symmetric divisions in the C. elegans epidermis perturbs robustness of stem cell number

Abstract: Biological systems are subject to inherent stochasticity. Nevertheless, development is remarkably robust, ensuring the consistency of key phenotypic traits such as correct cell numbers in a certain tissue. It is currently unclear which genes modulate phenotypic variability, what their relationship is to core components of developmental gene networks, and what is the developmental basis of variable phenotypes. Here, we start addressing these questions using the robust number of Caenorhabditis elegans epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 86 publications
5
53
0
Order By: Relevance
“…The development of the seam cells is canalized to the point of eutely, so that during normal development the balance of asymmetric and symmetric divisions maintains a constant seam cell number (Sulston and Horvitz, ). Variation in the number of seam cells can be used as a metric for phenotypic variation in animals subjected to genetic perturbation in addition to environmental stress (Mestek Boukhibar and Barkoulas, ; Katsanos et al, ). In C. elegans , we find that a number of DnaJs, not limited to ER‐associated chaperones, are involved in canalization.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the seam cells is canalized to the point of eutely, so that during normal development the balance of asymmetric and symmetric divisions maintains a constant seam cell number (Sulston and Horvitz, ). Variation in the number of seam cells can be used as a metric for phenotypic variation in animals subjected to genetic perturbation in addition to environmental stress (Mestek Boukhibar and Barkoulas, ; Katsanos et al, ). In C. elegans , we find that a number of DnaJs, not limited to ER‐associated chaperones, are involved in canalization.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer have been found that are required for eff-1 activation, which could also provide additional noise or variability into the cell fate decision. Studies have shown a lin-22 loss-of-function mutation decreases P3.p cell fusion frequencies (Katsanos et al, 2017;Schlager et al, 2006). LIN-22 codes for a Hairy/Enhancer of Split-related transcription factor, which was found to act in the Wnt pathway by repressing egl-18, a GATA transcription factor, also a repressor of cell fusion in the seam cells (Gorrepati et al, 2013;Katsanos et al, 2017;Wrischnik and Kenyon, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a lin-22 loss-of-function mutation decreases P3.p cell fusion frequencies (Katsanos et al, 2017;Schlager et al, 2006). LIN-22 codes for a Hairy/Enhancer of Split-related transcription factor, which was found to act in the Wnt pathway by repressing egl-18, a GATA transcription factor, also a repressor of cell fusion in the seam cells (Gorrepati et al, 2013;Katsanos et al, 2017;Wrischnik and Kenyon, 1997). Therefore, variations in not only the inhibitor molecules, but LIN-22 could create noise and variability that leads to stochastic eff-1 expression and cell fusion.…”
Section: Discussionmentioning
confidence: 99%
“…To construct a pseam::GFP::CAAX::unc-54 transgene, the GFP sequence was amplified using pPD93.65 as template and fused to the following sequence containing the CAAX motif using nested PCR 5’AAGGACGGAAAGAAGAAGAAGAAGAAGTCCAAGACCAAGTGCGTCATCATG3’. The GFP::CAAX fragment was then subcloned into pIR5 (Katsanos et al . 2017) via Gibson assembly.…”
Section: Methodsmentioning
confidence: 99%